Adjusted State Teacher Salaries and the Decision to Teach - Dan S. Rickman; Hongbo Wang; John V. Winters (Institute for the Study of Labor (IZA), 2015)
Using the 3-year sample of the American Community Survey (ACS) for 2009 to 2011, we compute public school teacher salaries for comparison across U.S. states. Teacher salaries are adjusted for state differences in teacher characteristics, cost of living, household amenity attractiveness and federal tax rates. Salaries of non-teaching college graduates, defined as those with occupations outside of education, are used to adjust for state household amenity attractiveness. We then find that state differences in federal tax-adjusted teacher salaries relative those of other college graduates significantly affects the share of education majors that are employed as teachers at the time of the survey.
Keywords: H75; I20; I28; J24; J31; R23; 330; teachers; teacher salaries; teaching profession; teacher retention